The Unemployment Problem A Norwegian Perspective - Holden, Steinar (OECD Economics Department Working Papers, 1997)
This paper lays out a simple open economy macromodel based on the recent literature on imperfect competition and equilibrium unemployment. It is shown that the NAIRU is not a clearcut concept in the open economy framework. Furthermore, it is argued that the self-correcting mechanisms in the economy are weak, so that the actual rate of unemployment may deviate considerably from the NAIRU over long periods. The theoretical discussion is illustrated by recent Norwegian experience. The paper also investigates the costs and benefits of incomes policies in unionised economies. Finally, there is a discussion of various aspects of the Norwegian labour market and Norwegian labour market policies ...